Evidence of porcine circovirus type 3 (PCV3) in a swine farm in Costa Rica - Chaverri, Laura (2022)
The presence of the pathogen Porcine Circovirus 3 (PCV3) is reported for the first time in Costa Rica in a swine farm located in the province of Cartago. The Real Time PCR technique was used. From a total of 56 pools of blood samples from animals with respiratory symptomatology and emaciation, 32 tested positive (57.14%) for PCV3, while 24 tested negative (42.86%). Only one case tested positive for PCV2 and negative for PCV3. The presence of this disease in the country must be monitored in order to know its epidemiology and its possible impact on the national swine herd.